A clinico-etiological profile of adult extrahepatic portal venous obstruction in patients from Northern India. Is it a novel subset of occult extrahepatic portal vein obstruction? - Zeeshan Ahmad Wani,; Mir Mohamad Muzzafer,; Khan Afaq Ahmad,; Lone Shaheen Nazir, (Asian Journal of Medical Sciences, 2024)
Background: Extrahepatic portal vein obstruction (EHPVO) is caused by occlusion and cavernomatous transformation of the portal vein. The EHPVO is well characterized in children. However, the same is not valid for adults. We aimed to evaluate the clinico-etiological profile along with the management of adult patients. Aims and Objectives: We evaluated the clinico-etiological profile along with the management and outcomes of adult patients presenting with EHPVO. Materials and Methods: In a descriptive, observational study, patients between ages 15 and 75 years diagnosed with EHPVO on ultrasonography abdomen were included in the study. Liver cirrhosis and malignancy were considered as an exclusion criterion. There was evaluation of clinical and imaging findings along with biochemical analysis, workup for thrombophilia, treatment given to the patients, and follow-up. Results: Out of total 109 patients enrolled in the study, the median age of patients was ±40.25. Main clinical features were dyspepsia, abdominal discomfort, and splenomegaly. Out of 109, 27.5% patients showed fatty liver and 5.5% had both splanchnic vein thrombosis and fatty liver. Idiopathic EHPVO in majority of patients (80%), adult EHPVO with polycythemia rubra vera in 7.33% patients, adult EHPVO with heterozygous MTHFR mutation in 7.33% patients, and adult EHPVO with antiphospholipid antibody in 3.66%. No mortality was seen in this 5-year observational study and majority of the patients, i.e., 96 (88.1%) did not require any treatment. Conclusion: Relatively benign nature of adult EHPVO was found in the selected group of patients. Majority of the cases in our study were idiopathic and few had positive thrombophilia profile.